Exploring European hydrogen demand variations under tactical uncertainty with seasonal hydrogen storage - Sebastian Emil Hummelen; Erlend Hordvei; Marianne Petersen; Stian Backe; Hongyu Zhang; Pedro Crespo del Granado (Energy Strategy Reviews)
Achieving a net-zero energy system in Europe by 2050 will likely require large-scale deployment of hydrogen and seasonal energy storage to manage variability in renewable supply and demand. This study addresses two key objectives: (1) to develop a modeling framework that integrates seasonal storage into a stochastic multi-horizon capacity expansion model, explicitly capturing tactical uncertainty across timescales; and (2) to assess the impact of seasonal hydrogen storage on long-term investment decisions in European power and hydrogen infrastructure under three hydrogen demand scenarios. To this end, the multi-horizon stochastic programming model EMPIRE is extended with tactical stages within each investment period, enabling operational decisions to be modeled as a multi-stage stochastic program. This approach captures short-term uncertainty while preserving long-term investment foresight. Results show that seasonal hydrogen storage considerably enhances system flexibility, displacing the need for up to 600 TWh/yr of dispatchable generation in Europe after 2040 and sizing down cross-border hydrogen transmission capacities by up to 12%. Storage investments increase by factors of 5–14, which increases the investments in variable renewables and improve utilization, particularly solar. Scenarios with seasonal storage also show up to 6% lower total system costs and more balanced infrastructure deployment across regions. These findings underline the importance of modeling temporal uncertainty and seasonal dynamics in long-term energy system planning.